Normality tests for statistical analysis in dentistry: a brief notes for researcher - Mohd Ibrahim, Mohamad Shafiq (IIUM Press, 2024)
In the realm of dentistry research, statistical analysis is essential to deriving relevant conclusions from gathered data. The normality of the data distribution is one basic assumption that is frequently evaluated. This is important since it helps choose the right statistical tests and guarantees the validity of the findings. These brief notes provide an understanding of numerous normality tests and how to apply them in statistical analysis, making it an invaluable resource for dental researchers. There are multiple ways to assess if a variable follows a normal distribution, including visual inspections and a variety of statistical tests which are not only applicable to dental research but also other research areas.